1989
DOI: 10.1111/j.1600-0765.1989.tb01792.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of neurochemical markers in gingiva obtained from periodontitis‐affected sites

Abstract: Immunohistochemical methods have been used to study the occurrence of neuronal markers in human gingiva from periodontitis-affected sites. In periodontitis-affected buccal gingiva densely distributed neurofilament (NF)-immunoreactive (IR) fiber bundles were observed in the deeper parts of the propria, while NF-IR single fibers occurred in the superficial propria and occasionally in the buccal epithelium. Periodontitis-affected gingiva obtained from interproximal sites showed only sparsely distributed NF-IR fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…MMPs are known to be produced by various immunoeffector cells, such as neutrophils, monocytes/macrophages, and fibroblast-like cells (Uitto et al, 2003;Sorsa et al, 2004), often influenced by the pro-inflammatory neuropeptides released from the closely apposed sensory nerves in various tissues (McGillis and Fernandez, 1999), including gingiva (Luthman et al, 1989). Animal studies have shown the existence of branched nerves innervating both intrapulpal and periodontal tissues (Foster and Robinson, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs are known to be produced by various immunoeffector cells, such as neutrophils, monocytes/macrophages, and fibroblast-like cells (Uitto et al, 2003;Sorsa et al, 2004), often influenced by the pro-inflammatory neuropeptides released from the closely apposed sensory nerves in various tissues (McGillis and Fernandez, 1999), including gingiva (Luthman et al, 1989). Animal studies have shown the existence of branched nerves innervating both intrapulpal and periodontal tissues (Foster and Robinson, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the pro-inflammatory neuropeptides released by sensory nerves co-ordinate the activities of the immune-effector cells (McGillis and Fernandez, 1999), and may play an important role in the pathogenesis of periodontitis (Luthman et al, 1989). Painful teeth with pulpitis have been shown to be associated with elevated levels in GCF of pro-inflammatory peptides, such as substance P (SP) and neurokinin A (NKA) (Awawdeh et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…With the recognition that peptidergic neurons extensively innervate the gingivae (Luthman et al, 1988(Luthman et al, , 1989, and the identification of neuropeptides in GCF (Linden et al, 1997(Linden et al, , 2002Lundy et al, 1999Lundy et al, , 2000bHanioka et al, 2000), it is becoming increasingly evident that periodontitis and indeed other orofacial inflammatory disorders may be modulated by imbalances in certain neuropeptides. The distribution of neurochemical markers in tissue obtained from gingivitis-and periodontitis-affected sites led Luthman et al (1989) and Bartold et al (1994) to suggest a possible role for neuropeptides in the pathogenesis of periodontitis. However, in addition to neuropeptides, the intensity and duration of inflammation in periodontal disease are also controlled by a complex regulatory network of inflammatory mediators and immune cells.…”
Section: (D) Neuropeptides and Periodontitismentioning
confidence: 99%
“…On the other hand, when Luthman et al (11) examined neurochemical markers in the gingivae from periodontitis-affecte and healthy sites in humans, they found no apparent differences in the number and density of nerve fibers with SP-or CGRP-IR.…”
Section: Discussionmentioning
confidence: 99%
“…However, the changes of gingival innervation in relation to gingivitis have previously only been described briefly. In human gingivae with periodontitis, Luthman et al (11) found a dense network of neurofilament-immunoreactive fibers. How-Correspondence to Teruo Tanaka, First Department of Oral Anatomy, Kyushu University Faculty of Dentistry, 61, Fukuoka, 812, Japan.…”
mentioning
confidence: 99%